MODEL PENINGKATAN KOMPETENSI DOSEN; PERAN KNOWLEDGE SHARING, MOTIVASI, DAN NEED FOR COGNITION DOSEN UNIVERSITAS TEUKU UMAR - Susanto; Hartoyo; Rizal Syarief (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Competence is a set of knowledge, skills, and behaviors that teachers or lecturers must possess, appreciate, and master in carrying out professional duties. Lecturers as professional educators are required to have competence as the spearhead of the teaching and learning process. Teuku Umar University (UTU), as one of the state universities in Aceh Province, is required to improve its lecturers' competence by looking at the role of knowledge sharing, motivation, and need-for-cognition of its lecturers. This study aimed to analyze the effect of knowledge sharing, motivation, and need for cognition on lecturers' competence at UTU by using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that knowledge sharing and need-for-cognition had a positive effect on the lecturers' commitment, while motivation had no positive effect on lecturer commitment. However, motivation had a positive effect on lecturers' knowledge sharing, while need-for-cognition had no positive effect on lecturers' knowledge sharing. Based on the research results, UTU should facilitate its lecturers to carry out knowledge sharing activities that could be implemented through knowledge management. As for need-for-cognition, it is expected that UTU would create a new cognitive need, such as holding new knowledge competitions or rewards for lecturers who find discoveries. Keywords: competence, knowledge sharing, motivation, need-for-cognition, SEM-PLS